Numerical Flow Characterization around a Type 209 Submarine Using OpenFOAM - Ruben J. Paredes; Maria T. Quintuña; Mijail Arias-Hidalgo; Raju Datla (Fluids, 2021)
The safety of underwater operation depends on the accuracy of its speed logs which depends on the location of its probe and the calibration thoroughness. Thus, probes are placed in areas where the flow of water is smooth, continuous, without high velocity gradients, air bubbles, or vortical structures. In the present work, the flow around two different submarines is numerically described in deep-water and near-surface conditions to identify hull zones where probes could be installed. First, the numerical setup of a multiphase solver supplied with OpenFOAM v7 was verified and validated using the DARPA SUBOFF-5470 submarine at scaled model including the hull and sail configuration at <semantics>H/D=5.4</semantics> and <semantics>Fr=0.466</semantics>. Later, the grid sensitivity of the resistance was assessed for the full-scale Type 209/1300 submarine at <semantics>H/D=0.347</semantics> and <semantics>Fr=0.194</semantics>. Free-surface effect on resistance and flow characteristics was evaluated by comparing different operational conditions. Results shows that the bow and near free-surface regions should be avoided due to high flow velocity gradient, pressure fluctuations, and large turbulent vortical structures. Moreover, free-surface effect is stronger close to the bow nose. In conclusion, the probe could be installed in the acceleration region where the local flow velocity is <semantics>15%</semantics> higher than the navigation speed at surface condition. A 4% correction factor should be applied to the probe readings to compensate free-surface effect.